OPTIMASI KEAMANAN DATA PENERIMAAN MAHASISWA MENGGUNAKAN AES-256, SHA-256, DAN BASE64 - Ahmad Halimi; Abu Tholib; Moh. Ainol Yaqin (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2024)
In this era of extraordinary information technology, data security is a priority, especially the process of admitting new students (PMB) to tertiary institutions. This process involves collecting sensitive personal data from thousands of prospective students each year. To protect this data, this research applies 256-bit Advanced Encryption Standard (AES), Secure Hash Algorithm 256 (SHA-256), and Base64 encryption methods. AES-256-CBC is known to be effective in maintaining data security with a high level of security. SHA-256 enhances security further by generating a unique hash that verifies data integrity. Meanwhile, Base64 converts binary data into a more manageable text format. This research also includes testing encryption and verification speed using the Laravel framework. The application of this method is expected to increase trust and meet strict data security standards in the PMB information system, guarantee comprehensive data protection and improve system integrity.